Studi Pemahaman Literasi Digital Serta Efek Domino Perkembangan Soft Skills Siswa Daerah Perbatasan - Siprianus Jewarut; Margaretha Lidya Sumarni Lidya (LP. Ma'arif Janggan Magetan, 2022)
This study aims to determine the understanding of digital literacy and the domino effect of the soft skills development of border area students. This research was conducted using a combination of quantitative methods, interviews and observations with a descriptive discussion model. Questionnaires were given to explore students' understanding of digital literacy, while interviews and observations aimed to determine students' soft skills activities. The object of the research was the 8th grade students of Tarsisia Bengkayang Middle School, West Kalimantan, with a total of 80 students as respondents. From the results of the questionnaire analysis, it shows that students' understanding of digital literacy is low with the percentage of students' answers being 80.00%. This has implications for student activities while playing gadgets, where from the results of the questionnaire it was found that 80.00% of student activities while playing gadgets only access entertainment content in the form of games, YouTube, Instagram and Tiktok while only 5% of students who use devices to study. A further impact of the lack of students' understanding of digital literacy is on the development of students' soft skills on the occasion of observation and interviews. It was found that the activities that students often do during recess at school are only playing with gadgets without socializing with friends, besides that students' sense of responsibility by helping Parents at home are becoming less and less because students are more busy playing with their gadgets.